Analysis of Gene Polymorphism CYP2C19 in the Lebanese Population Who Reside in Colombia (2018)
Background: The aim of this study is to determine the polymorphism of the CYP2C19 gene in the Lebanese population living in Colombia due to the lack of information and the importance of establishing its behavior which can predict a diminished or increased metabolism of medication related to it. Methods and Results: 109 Lebanese volunteers residents of Colombia were included, genotypes for the CYP2C19 were detected by polymerase Chain Reaction-PCR finding that the most frequent allele was *1 (73.4%), followed by *2 (26.6%) the allele *3 was not found in the studied population. Only fast metabolites were found because of the *1/*1 (73.4%) and *1/*2 (26.6%) genotypes, any *1/*3, *2/*2 or *3/*3 genotype were found. Conclusions: The results obtained show a similar behavior with the alleles frequencies of the previous studies made in Colombia, Africa, Europe and other American population. Knowing the genotype of the population is important for the selection and adjustment of the doses of the best medication to give the optimal treatment in medical practice. The pharmacogenetics will reduce the adverse reactions during medical treatment for a better and more accurate clinical approach.